Cannabidiol as Modulator of Spontaneous Adipogenesis in Human Adipose-Derived Stem Cells - Giovannamaria Petrocelli; Luca Pampanella; Provvidenza Maria Abruzzo; Sara Cruciani; Carlo Ventura; Silvia Canaider; Federica Facchin (Molecules)
Mesenchymal stem cells isolated from human adipose tissue (hASCs) are a promising tool for tissue repair due to their ability to differentiate into specific cell lineages. The possibility of modulating the adipogenic differentiation of hASCs is crucial in improving their therapeutic potential. This study aimed to investigate the effects of cannabidiol (CBD), a phytocannabinoid isolated from Cannabis sativa L., on hASCs. Few studies have evaluated its role in stem cell (SC) properties and their differentiation potential. hASCs were first treated with different concentrations of CBD (ranging from 0.1 to 10 μM) to assess its effects on viability, demonstrating that this molecule is non-toxic, except at the concentration of 10 μM. Subsequently, the role of CBD in the proliferation, metabolism and adipogenic potential of hASCs was analyzed. CBD promoted adipogenesis in a dose-dependent manner, even in the absence of differentiation medium. This result was evidenced by the presence of lipid vacuoles, the expression of adipogenic markers, cytoskeletal actin rearrangement and modulation in the expression of osteogenic genes. Although the results indicated a role of CBD in promoting hASC adipogenesis, further research will be needed to explore the mechanism of action of CBD in SC differentiation and to deepen its utility in SC-based approaches.